The Emerging Spectrum of Respiratory Diseases in the U.S. Cannabis Industry - Sack, Coralynn; Simpson, Christopher; Pacheco, Karin (Seminars in Respiratory and Critical Care Medicine, 2023)
While the cannabis industry is one of the fastest growing job markets in the United States and globally, relatively little is known about the occupational hazards that cannabis production workers face. Based on the closely related hemp industry and preliminary studies from recreational cannabis grow facilities, there is concern for significant respiratory exposures to bioaerosols containing microbial and plant allergens, chemicals such as pesticides, volatile organic compounds, and other irritant gases. Components of the cannabis plant have also recently been identified as allergenic and capable of inducing an immunoglobulin E-mediated response. Accumulating evidence indicates a spectrum of work-related respiratory diseases, particularly asthma and other allergic diseases. Disentangling causal relationships is difficult given the heterogeneity of mixed exposures, diagnostic challenges, and confounding by personal cannabis use. Despite and because of these uncertainties, better regulatory guidance and exposure controls need to be defined in order to reduce the risk of work-related disease.
Keywords: cannabis; allergens; occupational lung disease; occupational exposure